Tourism Pressure and Vegetation Dynamics in the Carpathian Mountains - Kasiyanchuk, Dmytro (Eco-Tourism and Sustainable Development, 2025)
This study investigates the impact of recreational tourism on vegetation dynamics in the Carpathians, focusing on the ecological effects of infrastructure expansion and seasonal tourist flows. Analysis of NDVI trends from 2015–2025 indicates overall high vegetation productivity, but with significant localized declines. From peak years (2017, 2021, 2024) to 2025, photosynthetically active cover decreased by about 12–13% in the most affected areas. Hotspots around Hoverla, Petros, and the Bukovel corridor showed even sharper reductions of 25–35%, linked to trampling, erosion, and construction. While warmer temperatures and higher moisture generally stimulate vegetation growth, the cumulative pressure of tourism—including ski slopes, roads, and concentrated visitor traffic—drives habitat fragmentation, reduced stability of vegetation edges, and slower regeneration of alpine meadows. Areas exposed to moderate use demonstrated greater resilience, highlighting the potential of adaptive management to reconcile tourism with ecosystem health. The research integrates NDVI time-series with spatial data on tourism intensity and climate parameters, offering a comprehensive picture of vegetation changes under anthropogenic stress. Its novelty lies in directly linking ecosystem responses to quantifiable tourism indicators, providing a basis for defining ecological carrying capacity. Findings underscore the urgent need for sustainable tourism policies tailored to vulnerable zones, especially the Yaremche–Bukovel corridor. Recommendations include integrating ecosystem services into planning, setting carrying capacity thresholds, and prioritizing conservation of alpine habitats. By connecting vegetation monitoring with tourism metrics, this study establishes a framework for balancing economic benefits with the long-term ecological integrity of mountain ecosystems, positioning the Carpathians as a key case for sustainable development under rising recreational pressure.